2013
DOI: 10.1016/j.yebeh.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and neuroethological studies of three antiepileptic drugs in the Genetic Audiogenic Seizure Hamster (GASH:Sal)

Abstract: Epilepsy modeling is essential for understanding the basic mechanisms of the epileptic process. The Genetic Audiogenic Seizure Hamster (GASH:Sal) exhibits generalized tonic-clonic seizures of genetic origin in response to sound stimulation and is currently being validated as a reliable model of epilepsy. Here, we performed a pharmacological and neuroethological study using well-known and widely used antiepileptic drugs (AEDs), including phenobarbital (PB), valproic acid (VPA), and levetiracetam (LEV). The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Other animal models of audiogenic epilepsy generated by artificial selection include the GAERS [19], the WAG/Rij [20] and the WAR [23], in which an auditory stimulus triggers the onset of audiogenic seizures. In all these models, different types of studies on seizures and pharmacological treatments have been conducted in the inferior colliculus as an epileptogenic nucleus and in auditory pathways [31,[74][75][76][77][78]. In the GASH/Sal model, previous studies have determined that susceptibility to developing the epileptic phenotype shows an autosomal recessive inheritance pattern [24].…”
Section: Plos Onementioning
confidence: 99%
“…Other animal models of audiogenic epilepsy generated by artificial selection include the GAERS [19], the WAG/Rij [20] and the WAR [23], in which an auditory stimulus triggers the onset of audiogenic seizures. In all these models, different types of studies on seizures and pharmacological treatments have been conducted in the inferior colliculus as an epileptogenic nucleus and in auditory pathways [31,[74][75][76][77][78]. In the GASH/Sal model, previous studies have determined that susceptibility to developing the epileptic phenotype shows an autosomal recessive inheritance pattern [24].…”
Section: Plos Onementioning
confidence: 99%
“…The control and GASH/Sal animals that were exposed to loud sound stimulation were individually placed within an acrylic cylinder to receive a single high-intensity acoustic stimulus for 10 s. The stimulus used in the high-intensity acoustic stimulation protocol was recorded using a high-pass filter (N500 Hz; microphone Bruel and Kjaer #4134 and preamplifier Bruel and Kjaer #2619), digitized above 4 kHz, and reproduced by a computer coupled to an amplifier (Fonestar MA-25T, Revilla de Camargo, Spain) and a tweeter (Beyma T2010, Valencia, Spain) in the upper portion of the arena. The delivered sound was a semirandom acoustic stimulus of 0-18 kHz with an intensity of 115 to 120 dB (Barrera-Bailón et al, 2013;López-López et al, 2017).…”
Section: Methodology Animalsmentioning
confidence: 99%
“…These animals reach their maximum degree of seizure susceptibility between the second and fourth month of life, which then gradually disappears (Muñoz et al, 2017), and their seizures have been characterized as complete sound-evoked reflex seizures (Carballosa-Gonzalez et al, 2013). Furthermore, several studies have reported the inheritance pattern (Muñoz et al, 2017), and the neuroanatomical substrates underlying audiogenic seizure susceptibility (Sánchez-Benito et al, 2017 as well as the anticonvulsant effects after antiepileptic drug administration (Barrera-Bailón et al, 2013. It has also been found that the GASH/Sal exhibits altered gene expression of early growth response genes 1 to 3 (Egr1, Egr2, and Egr3) in the IC, presumably as an effect of stress associated to seizures (López-López et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in addition to being able to reliably reproduce the objective symptoms and EEG features of the epilepsy syndrome, it is also able to respond to different antiepileptic drugs (AEDs), such as phenobarbital, valproic acid, and levetiracetam [112], so the GASH:Sal is a reliable animal model of epilepsy.…”
Section: Relevance Of the Modelmentioning
confidence: 99%